Maximum production of methanol in a pilot-scale process - Son, Minji; Park, Myung June; Kwak, Geunjae; Park, Hae Gu; Jun, Ki Won (Korean Journal of Chemical Engineering, 2018)
Mathematical models for both bench- and pilot-scale methanol synthesis reactors were developed by estimating the overall heat transfer coefficients due to different heat transfer characteristics, while the effectiveness factor was fixed because the same catalysts were used in both reactors. The overall heat transfer coefficient of a pilot-scale reactor was approximately twice that of a bench-scale reactor, while the estimate from the correlation reported for the heat transfer coefficient was 1.8-times higher, indicating that the values determined in the present study are effective. The model showed that the maximum methanol production rate of approximately 16 tons per day was achievable with peak temperature maintained below 250 °C in the open-loop case. Meanwhile, when the recycle was used to prevent the loss of unreacted gas, peak temperature and production rate decreased due to low CO and CO2 fraction in the recycled stream at the same space velocity as the open-loop operation. Further analysis showed that, since the reaction was in the kinetic regime, the production rate could be maximized up to 18.7 tons per day by increasing the feed flowrate and inlet temperature despite thermodynamically exothermic reaction.
Keywords: Effectiveness Factor; Maximum Production; Methanol; Overall Heat Transfer Coefficient; Reactor Modeling